In Silico Study of Cephalosporin against Penicillin binding Protein - Zikri, Tan Muhamad; Wijianto, Bambang; Sari, Rafika (Universitas Tanjungpura, 2024)
The Antibiotic resistance is increasing in almost all classes of antibiotics, including cephalosporins. The purpose of research is to find the QSAR equation of cephalosporin against penicillin binding protein and obtain the modified compound which is predicted to have better activity than other cephalosporin drugs through the QSAR equation and docking study. The research was started by analyzing QSAR using the BUILDQSAR program, then the QSAR equation was obtained which was used to design new compounds from the cephalosporin group that were more potent. The results of the new design cephalosporin are docked using the Autodock Vina program to determine the antibacterial potential and binding to receptors. Receptor validation was using the pymol program. The best formula of QSAR is -LOG 1/IC50 = - 0.0419 ( ± 0.0109) HYDRATION ENERGY - 6.2516 ( ± 3.0111) qN10 + 0.0523 ( ± 0.0159) POLARIZABILITY - 5.2468 ( ± 1.3254) qC2 + 0.6014 ( ± 0.9884) qC3 + 0.0020 ( ± 0.0010) HEAT OF FORMATION - 5.5042 ( ± 1.6295) qN7 + 2.1201 ( ± 0.7903). Three cephalosporin-modified ligands from QSAR equation and study of literature is named TBS 1, TBS 2, TBS 3. The Ligands is modified by the subtitution of electron withdrawing group in C3 and subtitution of structure that increase the antibacterial activity in C9 and C11. Log1/IC50 score of TBS 1, TBS 2 and TBS 3 are 8.4, 7.9 and 6.4 which is higher than another cephalosporin's derrivates Log1/IC50 score. four ligands including cefmetazole as control positive are docked with PBP2a as receptor. The score docking (afinity) of the TBS 1, TBS 2, TBS 3 and cefmetazole are -7.5, -7.4 -7.5 and 6.8. It Shows the cephalosporin-modified ligand have better activity than cefmetazole against PBP2a receptor. The conclusion of the research is the QSAR equation's is found and three cephalosporin-modified is predicted to have better antibacterial activity.